Recommendations from the European Society for Blood and Marrow Transplantation (EBMT) for a curriculum in hematopoietic cell transplantation. (December 2018) - Mohty, Mohamad; Duarte, Rafael; Kuball, Jurgen; Bader, Peter; Basak, Grzegorz; Bonini, Chiara; Carreras, Enric; Chabannon, Christian; Dufour, Carlo; Gennery, Andrew; Lankester, Arjan; Lanza, Francesco; et al.
Abstract Hematopoietic cell transplantation (HCT) is increasingly used worldwide. This treatment approach is complex and requires specific knowledge and training. The European Society for Blood and Marrow Transplantation (EBMT) identified the need for a set of international recommendations for the clinical training of physicians to qualify them as being competent in performing HCT procedures as well as novel cellular immune therapies and taking care of such patients. The goal is to implement an EBMT HCT-focused global curriculum (EBMT-GC) that can serve as a tool for the development of the HCT sub-specialty worldwide. Despite the diversity and heterogeneity of health and educational systems around the globe, this set of recommendations can be fairly adopted by any national educational and health authorities and can be adjusted to specific conditions and resources of a given country, if needed. The ultimate goal of the EBMT-GC is to define standards for personal knowledge in allogeneic stem cell transplantation for physicians worldwide in order to ensure that all patients will receive treatment by well-trained physicians.